THE IMPLEMENTATION OF CLOZE STRATEGY TO TEACH DESCRIPTIVE TEXT READING FOR EIGHTH GRADE STUDENT OF SMP NEGERI 1 WONOASRI - Diani Rochmawati; Brigitta Septarini Rahmasari (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
Reading is one of the abilities of the students to master in English lessons. In reading a text students must be able to absorb the information conveyed by the author to the reader, because the essence of reading is knowing the information expressed in the text. Achieving the goal of reading in the application encounters several obstacles, including vocabulary mastery and low motivation to read to students. Knowing this, researchers used a reading strategy, cloze strategy. The purpose of this study was to determine the application of reading strategies using cloze strategy in reading descriptive text along with weaknesses and excesses. The researcher used qualitative descriptive research method to answer the hypothesis in the formulation of the problem. It can be concluded that the application of this reading strategy in the teaching and learning process has three steps, namely: pre-activities, whilst-activities and post-activities. While the advantages of this strategy are students enjoy reading lessons and students can absorb information in the text easily, while the weakness is the class becomes noisy in some activities.